Exploring the language layer of the dānastuti genre - Pinault, Georges-Jean (Lingua Posnaniensis, 2019)
The linguistic variedness of the ancient Vedic texts is a well-known fact. This can be observed within the Ṛgveda itself, the most ancient collection of hymns, and if one compares the language of the Ṛgveda with that of the Atharvaveda. Glimpses of Vedic dialects can be detected in several passages and words, although the poetic language displays a high degree of convention and normalisation. Among the hymns of the Rigveda few specific features can be attributed to the different families of bards, even though one can surmise that they belonged to different regions of the Vedic world. It is also likely that some families or so-called “branches” were linguistically mixed. The hymns resort to different genres of discourse. The dānastuti, lit. ‘praise of the gift’, marks a distinct part of the poetic competence. The passages in question, which are often limited to a single stanza, although others are more developed, making up a substantial part of the poem, are devoted to praise of the generosity of the patron, who is expected to reward the poet appropriately for his work. A comprehensive survey of these parts of the hymns of the Rigveda was made in the dissertation of Manilal Patel (1929), a student of Karl F. Geldner. This meritorious book describes mostly cultural, historical and ritual features. On the other hand, the familiar, and in cases crude or mischievous, tone of these pieces has been noted by several commentators of the Rigveda. It would be too simple, however, to consider that these parts faithfully reflect everyday speech. The paper aims to explore the linguistic traits of the dānastutis which contrast with the standard layer of the Ṛgvedic language at all levels: phonology, morphology, syntax, vocabulary. On the level of stylistics and poetics, it will be shown that the phraseology of the dānastutis relies on sophisticated devices derived from the standard phraseology which was used otherwise for the praise of the gods and goddesses in the core of the hymns.